Occurrence of Escherichia coli in mussels (Mytilus galloprovincialis) from farms in Boka Kotorska Bay, Southern Adriatic Sea. Issue 1 (October 2021) - Grkovic, N; Djuric, S; Sindjic, M; Velebit, B; Suvajdzic, B; Dimitrijevic, M
Abstract: This study reports the occurrence of Escherichia coli in 243 mussel samples collected along the Boka Kotorska Bay (six harvesting areas), which is located in the Southern Adriatic Sea. Bivalve molluscs can concentrate contaminants from their water environment, so because of that, determination of E. coli levels is an important parameter for microbial pollution assessment in the investigated areas. The number of E. coli ranged between <18 MPN/100 g to 16 x 10 3 MPN/100 g of mussel soft tissues. In 243 bivalve mollusc samples, analysed during the period 2018-2019, 68.3% of them had low contamination levels, i.e. ≤ 230 MPN E. coli /100 g; 31.3% had between 230 and 4600 MPN E. coli /100 g, and 0.4% had > 4600 MPN E. coli /100 g. Statistical analysis of the number of E. coli in mussels established that the mussel farm vl. Duško Vlahović (M5) had the highest mean E. coli levels (949.00 ± 2541 MPN E. coli /100 g), while the lowest mean level was recorded in Boka mussels (M1) (149.20 ± 258.80 MPN E. coli /100 g). Boka Kotorska bay is classified as a Class B mussel production area because it has 32.9% of samples with E. coli MPN values between the 20-230 MPN/100g.